2024
DOI: 10.1109/tnsre.2023.3346639
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Evaluation of Upper Limb Motor Function for Stroke Patients Based on Belief Rule Base

Shuang Li,
Zhanli Wang,
Xiaojing Yin
et al.

Abstract: In the process of rehabilitation treatment for stroke patients, rehabilitation evaluation is a significant part in rehabilitation medicine. Researchers intellectualized the evaluation of rehabilitation evaluation methods and proposed quantitative evaluation methods based on evaluation scales, without the clinical background of physiatrist. However, in clinical practice, the experience of physiatrist plays an important role in the rehabilitation evaluation of patients. Therefore, this paper designs a 5 degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies have shown that 1–2 weeks after the onset of stroke represent the acute phase, equivalent to Brunnstrom stages I and II; 3–4 weeks post-stroke indicate the early recovery stage, equivalent to Brunnstrom stages II and III; 4–12 weeks post-stroke signify the mid-recovery stage, equivalent to Brunnstrom stages III and IV; and 4–6 months post-stroke denote the late recovery stage, equivalent to Brunnstrom stages V and VI for patients ( Li et al, 2023 ). Based on this medical knowledge the number of training weeks under different Brunnstrom stage of the patients was prescribed.…”
Section: Cycle Plan Inference Model Construction Based On Rbrmentioning
confidence: 99%
“…Studies have shown that 1–2 weeks after the onset of stroke represent the acute phase, equivalent to Brunnstrom stages I and II; 3–4 weeks post-stroke indicate the early recovery stage, equivalent to Brunnstrom stages II and III; 4–12 weeks post-stroke signify the mid-recovery stage, equivalent to Brunnstrom stages III and IV; and 4–6 months post-stroke denote the late recovery stage, equivalent to Brunnstrom stages V and VI for patients ( Li et al, 2023 ). Based on this medical knowledge the number of training weeks under different Brunnstrom stage of the patients was prescribed.…”
Section: Cycle Plan Inference Model Construction Based On Rbrmentioning
confidence: 99%